Comparison of the Pentax Airwayscope, Glidescope Video Laryngoscope, and Macintosh Laryngoscope During Chest Compression According to Bed Height. Issue 5 (February 2016) - Kim, Wonhee; Lee, Yoonje; Kim, Changsun; Lim, Tae Ho; Oh, Jaehoon; Kang, Hyunggoo; Lee, Sanghyun
Abstract : Abstract: We aimed to investigate whether bed height affects intubation performance in the setting of cardiopulmonary resuscitation and which type of laryngoscope shows the best performance at each bed height. A randomized crossover manikin study was conducted. Twenty-one participants were enrolled, and they were randomly allocated to 2 groups: group A (n = 10) and group B (n = 11). The participants underwent emergency endotracheal intubation (ETI) using the Airwayscope (AWS), Glidescope video laryngoscope, and Macintosh laryngoscope in random order while chest compression was performed. Each ETI was conducted at 2 levels of bed height (minimum bed height: 68.9 cm and maximum bed height: 101.3 cm). The primary outcomes were the time to intubation (TTI) and the success rate of ETI. The P value for statistical significance was set at 0.05 and 0.017 in post-hoc test. The success rate of ETI was always 100% regardless of the type of laryngoscope or the bed height. TTI was not significantly different between the 2 bed heights regardless of the type of laryngoscope (all P > 0.05). The time for AWS was the shortest among the 3 laryngoscopes at both bed heights (13.7 ± 3.6 at the minimum bed height and 13.4 ± 4.7 at the maximum bed height) (all P < 0.017). The TTI of Glidescope video laryngoscope was not significantly shorter than that of Macintosh laryngoscope at the minimum height (17.6 ± 4.0 vs 19.6 ± 4.8; P = 0.02). The bed height, whether adjusted to the minimum or maximum setting, did not affect intubation performance. In addition, regardless of the bed height, the intubation time with the video laryngoscopes, especially AWS, was significantly shorter than that with the direct laryngoscope during chest compression.